Z-oo9 Success rate evaluation of autogenous bone grafts and dental implants installed at maxillary sinus area - Salzedas, LM; Carneiro, GP; Fontão, FGK; Bassi, APF (ARCHIVES OF HEALTH INVESTIGATION, 2015)
Objectives: The surgery of the maxillary sinus elevation is considered an excellent option for the rehabilitation treatment of patients who present maxilary sinus pneumatization. Methods: Was conducted a longitudinal study with 41 patients from ILAPEO, who presents maxilary sinus pneumatization with evaluation of 51 surgeries of maxillary sinus elevation using autogenous bone grafts from oblique line. One hundred and seven implants were installed and twenty-eight of them were immediate. Results: The success rate was achieved with respect to the bone graft with 98.04 %.The implants placed immediately or after the grafting, succeeded with 92.86% and 94.59% respectively with no statistically significant differences between both. Conclusions: Surgery for bone graft and immediate installation are considered a reliable alternative treatment for both anatomical and physiological tissue structures and are suitable for the good stability of the implants.